Real-Life Utility of Basophil Activation Test in the Diagnosis of Immediate Hypersensitivity Drug Reactions - Dimitra Koumaki; Stamatios Gregoriou; Georgios Evangelou; Alexander Katoulis; Marios Papadakis; Sabine Elke Krueger-Krasagakis; Aikaterini Doxastaki; Dimitrios Mylonakis; Konstantinos Krasagakis (Adis, Springer Healthcare, 2023)
Abstract Introduction The basophil activation test (BAT) is a flow cytometry laboratory technique that assesses the level of activation indicators expressed on the surface of basophils. We conducted a real-life study in a prospective cohort of patients with reported drug hypersensitivity reactions to determine the true relevance of BAT as a diagnostic tool for assessing immediate hypersensitivity reactions to medicines. Methods We prospectively assessed individuals with clinical suspicion of immediate hypersensitivity reactions to drugs over a 2-year period. The allergological evaluation was carried out in accordance with European Academy of Allergy and Clinical Immunology (EAACI) guidance. All patients underwent BAT using the activation marker CD63. Results In total 13 patients with 54 reported immediate drug hypersensitivity reactions to medications were included in this study. Twelve were female (92.3%) and one was male (7.70%). The mean ± SD age of the patients was 47.31 ± 19.94 years. Antibiotics were tested in 35.2% (19/54) of patients, corticosteroids in 24.1% (13/54), iodinated contrast medium in 14.8% (8/54), and NSAIDs in 5.6% (3/54). There was no correlation between the BAT results and the age of patients, gender, type of medication, or time interval between the allergic reaction and BAT procedure. The sensitivity of BAT 5% CD63+ basophils to drugs was 97.6%, specificity was 96% for drug allergies, positive predictive value (PPV) was 94.3%, and negative predictive value (NPV) was 95.2%. Conclusions The sensitivity of BAT for drug allergies is limited, but it can nevertheless be very helpful before contemplating provocation testing in cases of life-threatening drug allergies where patients cannot be rechallenged or in cases of medications for which no other tests are available or their results are ambiguous.